2018
DOI: 10.2305/iucn.ch.2017.erl.1.en
|View full text |Cite
|
Sign up to set email alerts
|

European Red List of Lycopods and Ferns

Abstract: Hottentot Fern (Thelypteris pozoi) is a widespread species, although in Europe it is only found in the Macaronesian islands, Spain and France, where it is usually found near the sea. It has been assessed as Least Concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
2
5
0
4
Order By: Relevance
“…In common with the results of several other European Red Lists (e.g. vascular plants (Allen et al, 2014;Bilz et al, 2011;García Criado et al, 2017), some of the highest levels of endemism are found in the main mountain This Macaronesian endemic can be found at high elevations in cloud forest where the environment is made more favourable by the trade winds and also on rocks and cliffs, while on the north-eastern coast of Tenerife the species occurs at lower elevations (200-400 m) in the remaining patches of thermophilous forest. The species also infrequently grows in the region's famous Laurisilva forests.…”
Section: Distribution Of Endemic Speciessupporting
confidence: 84%
See 1 more Smart Citation
“…In common with the results of several other European Red Lists (e.g. vascular plants (Allen et al, 2014;Bilz et al, 2011;García Criado et al, 2017), some of the highest levels of endemism are found in the main mountain This Macaronesian endemic can be found at high elevations in cloud forest where the environment is made more favourable by the trade winds and also on rocks and cliffs, while on the north-eastern coast of Tenerife the species occurs at lower elevations (200-400 m) in the remaining patches of thermophilous forest. The species also infrequently grows in the region's famous Laurisilva forests.…”
Section: Distribution Of Endemic Speciessupporting
confidence: 84%
“…In comparison with other groups that have been assessed on a European scale, trees are among the most threatened species in Europe. Other plant groups that have been assessed are: 'policy plants', crop wild relatives, aquatic plants (Bilz et al, 2011), medicinal plants (Allen et al, 2014) and lycopods and ferns (García Criado et al, 2017). There is some overlap of the species included in these reports, but the result still shows that with 42% threatened species, trees have the highest proportion of threatened species, apart from 'policy plants'.…”
Section: Comparison With Other European Red Listsmentioning
confidence: 99%
“…Figura 6. Evaluación de especies amenazadas según la Lista Roja de Licopodios y helechos de UICN (García Criado et al 2017) respecto al grado de rareza en el Arco de Alborán (LC: preocupación menor, en verde; NT: casi amenazadas, en azul; VU: vulnerable, en amarillo; EN: en peligro, naranja; CR: en peligro crítico, rojo). Las barras bordeadas en negro corresponden a taxones que instituciones regionales, nacionales o internacionales han considerado amenazadas en distintos grados.…”
Section: Figure 5 Principal Components Analysis Of the Environmental Variables (Above) And The Pteridofloristic Indices (Below) Forunclassified
“…Factores geográficos y epiontológicos convergen en la definición de la pteridoflora del Arco de Alborán presentando una alta diversidad florística de helechos y afines (Dudley 2008), si bien más de la mitad de ellos con un alto o muy alto grado de rareza en la región. IUCN ha publicado recientemente una 'Lista Roja de lycopodios y helechos europeos' (García Criado et al, 2017). De los táxones aquí citados el 91% se consideran como de 'preocupación menor' (LC), 4 como 'casi amenazadas' (NT, Culcita macrocarpa, Dryopteris tyrrhena, Paragymnopteris marantae y Pteris incompleta), una especie como vulnerable (VU, Marsilea strigosa Willd.…”
Section: Conservaciónunclassified
“…• European Red List of Lycopods and Ferns, 2017• European Red List of Saproxylic Beetles, 2018• European Red list of Terrestrial Molluscs: slugs, snails, and semi-slugs, 2019• European Red list of Trees, 2019• European Red list of Selected Endemic Shrubs, 2019 Based on other European Red List assessments, 59% of freshwater molluscs, 40% of freshwater fishes, 28% of grasshoppers, crickets and bush-crickets, 23% of amphibians, 20% of reptiles, 20% of ferns and lycopods, 17% of mammals, 16% of dragonflies, 13% of birds, 9% of butterflies and bees, 8% of aquatic plants and 2% of medicinal plants are threatened at the European level IUCN, 2015;Hochkirch et al, 2016;García Criado et al, 2017). Additional European Red Lists assessing a selection of species showed that 22% of terrestrial molluscs, 16% of crop wild relatives and 18% of saproxylic beetles are also threatened Bilz et al, 2011;Cálix et al, 2018).…”
mentioning
confidence: 99%